Second Life for dummies - Robbins, Sarah (--For dummies., 2008)
You've heard all about Second Life. Maybe you've already jumped with both feet--and gotten stuck. Or maybe you're a Second Life veteran who wants to build something or run a business. Fear not! Second Life For Dummies is hear to hold your hand, pat your back, and cheer you on through this new and enchanting reality. Written by a pair of Second Life old timers, this easy-to-use, flip-and-find guide is packed with expert advice, seasoned insight, and handy tips and tricks to get you moving fast. You'll find out how to set up your account, create an avatar, meet people and socialize, and find your comfort zone and stay in it. But it's a big world out there, so with fantastic lists of cool places, answers to big questions, and supplemental software, Second Life For Dummies is your ticket to a great virtual adventure.